Humanin and Age-Related Diseases: A New Link? - Gong, Zhenwei; Tas, Emir; Muzumdar, Radhika (Frontiers in Endocrinology, 2014)
Humanin (HN) is 24-amino acid mitochondria-associated peptide. Since its initial discovery over a decade ago, a role for HN has been reported in many biological processes such as apoptosis, cell survival, substrate metabolism, inflammatory response and response to stressors such as oxidative stress, ischemia and starvation. HN and its potent analogs have been shown to have beneficial effects in many age-related diseases including Alzheimer’s disease (AD), stroke, diabetes, myocardial ischemia and reperfusion (MI-R), atherosclerosis, amyotrophic lateral sclerosis (ALS) and certain types of cancer both in vitro and in vivo. More recently, an association between HN levels, growth hormone/ insulin-like growth factor-1 (GH/IGF axis) and life span was demonstrated using various mouse models with mutations in the GH/IGF axis. The goal of this review is to summarize the current understanding of the role of HN in aging and age-related diseases.